Assessment of Water Shortage Situations in Lower Nam Pong Basin under Climate Change - Pawattana, Chalermchai; Panasoontorn, Sirikoon; Poopiwkham, Satit; Ikhwali, Muhammad Faisi (Naresuan University Journal: Science and Technology (NUJST); Vol 29 No 4 (2021): October-December 2021DO - 10.14456/nujst.2021.35, 2021)
Lower Nam Pong basin experiences scarcity of water demand for most part of the year. This paper aimed to evaluate the reliability and vulnerability of water resources in basin under a changing climate and growing water demand. To facilitate simulation, ECHAM5 and high temperature change scenarios was utilized in conjunction with Water Evaluation and Planning (WEAP) to allocate water for each sector to meet future water demand. Results show that the gap between demand and supply grew dramatically for high temperature change scenario with total water shortage of 13,530 MCM over 30 years while water shortage of ECHAM5 scenario was 1,347 MCM. Vulnerability for high temperature change scenario increased with values of 10.52 MCM/unsatisfactory day in which more than two times comparison to baseline. Additionally, the study confirmed that the WEAP model can be applied to assess water shortage for water resources planning in the Lower Nam Pong basin. Keywords: WEAP, Reliability, Vulnerability, ECHAM5, High temperature change